The LGB Mormon Paradox: Mental, Physical, and Self-Rated Health Among Mormon and Non-Mormon LGB Individuals in the Utah Behavioral Risk Factor Surveillance System. Issue 6 (12th May 2017) - Cranney, Stephen
ABSTRACT: Much of the literature on mental and physical health among religious LGB individuals has relied on small- N convenience samples. This study takes advantage of a unique, large- N, population-based dataset to test the relationship between religious identity, religious activity, and health, with a specific emphasis on Utah Mormons. In a surprising finding, Mormon LGBs report better mental health than non-Mormon LGBs, while their self-rated and physical health is not significantly different. However, there is some evidence that Mormon LGBs derive fewer health benefits from church attendance than their non-LGB Mormon counterparts. These results may nuance the conventional wisdom regarding the health dynamics of LGB individuals who identify with a conservative, heteronormative religious tradition, and plausible explanations are discussed.